Effects of various controlled ovarian hyperstimulation protocols and surgery on pregnancy outcomes in women with endometriosis - Han Zeng; Yanbin Wang (Gynecological Endocrinology)
Endometriosis is a common gynecological condition in women of childbearing age that causes symptoms such as menstrual changes and dysmenorrhea, and is also a major cause of infertility. Therefore, women with endometriosis usually need to use assisted reproductive technology (ART), such as in vitro fertilization or intracytoplasmic sperm injection, to increase their chances of conceiving. Numerous clinical observations and studies have indicated that endometriosis can affect the success of ART, such that women with endometriosis who use ART have a lower live-birth rate than those without endometriosis who use ART. Therefore, this article reviews the impact of various controlled ovarian hyperstimulation protocols and surgery on the pregnancy outcomes of women with endometriosis using ART to explore the selection of individualized treatment.